Women's Trade Union League badge, 1919 (1919)
1919 1918-1939 "Women's Trade Union League badge, 1919" [T0200.jpg], 1919 Women's Trade Union League badge, 1919 carrying the League's motto "Lose not those things that we have wrought". The badge also has initials of the League's leaders, Emma Paterson and Lady Emilia Francis Strong Dilke. The badge was presented at the Annual Conference of Delegates to the TUC in which women were employed. This copy of the badge held in the TUC Library Collections was awarded to Ann Loughlin of the United Garment Workers Union in 1919 because 'women's membership of the union had increased by over 20,000 during the past year'. Apart from a few commemorative presentations, only one badge was awarded each year. After the WTUL merged with the TUC in 1921, the TUC reinstated the award of a Women's Gold Badge at Congress in 1926.